Pengaruh Profitabilitas, Likuiditas, Nilai Tukar, Inflasi, Suku Bunga dan Leverage Terhadap Financial Distress pada Perusahaan Manufaktur Makanan dan Minuman yang Terdaftar pada BEI Periode 2019 - 2021 - Suriani, Elvi Sri Rahayu; Asmeri, Rina; Lady Silvera, Dica (Fakultas Ekonomi, Universitas Ekasakti, 2024)
This study aims to analyze and determine the effect of Profitability, Liquidity, Exchange Rate, Inflation, Interest Rates and Leverage on the Financial Distress of Food and Beverage Manufacturing Companies Listed on the IDX between 2019 - 2021. Techniques for collecting data use documentation. While the type of data is quantitative using secondary data. For the population using Food and Beverage Manufacturing Companies listed on the IDX for the 2019-2021 period, totaling 30 companies where the sampling is purposive sampling so that the total sample is 10 companies x 3 years = 30 financial statements. Then the data analysis uses multiple linear regression analysis, coefficient of determination, as well as t test and F test. The following are the results of the study (1) Profitability partially significantly affects financial distress. (2) Liquidity partially significantly affects financial distress. (3) The exchange rate partially does not significantly affect financial distress. (4) Inflation partially does not significantly affect financial distress. (5) Interest rates partially do not significantly affect financial distress. (6) Leverage partially does not significantly affect financial distress. (7) Profitability, liquidity, exchange rate, inflation, interest rates and leverage significantly affect financial distress.